3 4 6 9 13 18 24 31 39 48 58
+1 +2 +3 +4 +5 +6 +7 +8 +9 +10
<h2>
Answer:</h2>
The derivative of the function f(x) is:
![f'(x)=-2x](https://tex.z-dn.net/?f=f%27%28x%29%3D-2x)
<h2>
Step-by-step explanation:</h2>
We are given a function f(x) as:
![f(x)=5-x^2](https://tex.z-dn.net/?f=f%28x%29%3D5-x%5E2)
We have:
![f(x+h)=5-(x+h)^2\\\\i.e.\\\\f(x+h)=5-(x^2+h^2+2xh)](https://tex.z-dn.net/?f=f%28x%2Bh%29%3D5-%28x%2Bh%29%5E2%5C%5C%5C%5Ci.e.%5C%5C%5C%5Cf%28x%2Bh%29%3D5-%28x%5E2%2Bh%5E2%2B2xh%29)
( Since,
)
Hence, we get:
![f(x+h)=5-x^2-h^2-2xh](https://tex.z-dn.net/?f=f%28x%2Bh%29%3D5-x%5E2-h%5E2-2xh)
Also, by using the definition of f'(x) i.e.
![f'(x)= \lim_{h \to 0} \dfrac{f(x+h)-f(x)}{h}](https://tex.z-dn.net/?f=f%27%28x%29%3D%20%5Clim_%7Bh%20%5Cto%200%7D%20%5Cdfrac%7Bf%28x%2Bh%29-f%28x%29%7D%7Bh%7D)
Hence, on putting the value in the formula:
![f'(x)= \lim_{h \to 0} \dfrac{5-x^2-h^2-2xh-(5-x^2)}{h}\\\\\\f'(x)=\lim_{h \to 0} \dfrac{5-x^2-h^2-2xh-5+x^2}{h}\\\\i.e.\\\\f'(x)=\lim_{h \to 0} \dfrac{-h^2-2xh}{h}\\\\f'(x)=\lim_{h \to 0} \dfrac{-h^2}{h}+\dfrac{-2xh}{h}\\\\f'(x)=\lim_{h \to 0} -h-2x\\\\i.e.\ on\ putting\ the\ limit\ we\ obtain:\\\\f'(x)=-2x](https://tex.z-dn.net/?f=f%27%28x%29%3D%20%5Clim_%7Bh%20%5Cto%200%7D%20%5Cdfrac%7B5-x%5E2-h%5E2-2xh-%285-x%5E2%29%7D%7Bh%7D%5C%5C%5C%5C%5C%5Cf%27%28x%29%3D%5Clim_%7Bh%20%5Cto%200%7D%20%5Cdfrac%7B5-x%5E2-h%5E2-2xh-5%2Bx%5E2%7D%7Bh%7D%5C%5C%5C%5Ci.e.%5C%5C%5C%5Cf%27%28x%29%3D%5Clim_%7Bh%20%5Cto%200%7D%20%5Cdfrac%7B-h%5E2-2xh%7D%7Bh%7D%5C%5C%5C%5Cf%27%28x%29%3D%5Clim_%7Bh%20%5Cto%200%7D%20%5Cdfrac%7B-h%5E2%7D%7Bh%7D%2B%5Cdfrac%7B-2xh%7D%7Bh%7D%5C%5C%5C%5Cf%27%28x%29%3D%5Clim_%7Bh%20%5Cto%200%7D%20-h-2x%5C%5C%5C%5Ci.e.%5C%20on%5C%20putting%5C%20the%5C%20limit%5C%20we%5C%20obtain%3A%5C%5C%5C%5Cf%27%28x%29%3D-2x)
Hence, the derivative of the function f(x) is:
![f'(x)=-2x](https://tex.z-dn.net/?f=f%27%28x%29%3D-2x)
Answer: In my opinion you could just shorten the number of orders so that it's not so long.
Explanation: The numbers can be from every 20 orders so 900, 920, 940...so on.
Answer:
n= 36
Step-by-step explanation:
18=n-18 (add 18 to both sides of the equation, 18 and -18 cancel out)
36=n